Polystachya orophila (Orchidaceae, Polystachynae), a new species from tropical West Africa, and clarification on the nomenclature and taxonomy of P. microbambusa - Bidault, Ehoarn; Lowry, Porter P.; Stévart, Tariq (Phytotaxa, 2016)
Polystachya orophila, a new species of Orchidaceae, is described based on specimens collected during the baseline study of the Guinean Nimba Mountains for the environmental impact assessment for a proposed mining project. While material belonging to this species was mentioned as early as 1920 by Chevalier, it has historically been confused with P. microbambusa, from which it differs by its typically Polystachya-like clustered pseudobulbs, placing it in P. sect. Polystachya, whereas P. microbambusa has pseudobulbs successively growing on top of one another, forming developed and persistent stems, and is the sole representative of P. sect. Dimorphocaules. The complex taxonomic and nomenclatural history of P. microbambusa is also clarified. For both taxa we provide a morphological description as well as information on distribution, habitat, and phenology, an IUCN conservation status assessment using the Red List criteria, and a distribution map, along with a dichotomous key that also includes the most similar members of P. sect. Polystachya.